Experimental and computational techniques in soft condensed matter physics - Olafsen, Jeffrey S., 1970- (New York : Cambridge University Press, 2010)
"Soft condensed matter physics relies on a fundamental understanding at the interface between physics, chemistry, biology, and engineering for a host of materials and circumstances that are related to, but outside, the traditional definition of condensed matter physics. Featuring contributions from leading researchers in the field, this book uniquely discusses both the contemporary experimental and computational manifestations of soft condensed matter systems. From particle tracking and image analysis, novel materials and computational methods, to confocal microscopy and bacterial assays, this book will equip the reader for collaborative and interdisciplinary research efforts relating to a range of modern problems in nonlinear and non-equilibrium systems. It will enable both graduate students and experienced researchers to supplement a more traditional understanding of thermodynamics and statistical systems with knowledge of the techniques used in contemporary investigations"--
Machine generated contents note: 1. Microscopy of soft materials Eric R. Weeks; 2. Computational methods to study jammed Systems Carl F. Schrek and Corey S. O'Hern; 3. Soft random solids: particulate gels, compressed emulsions and hybrid materials Anthony D. Dinsmore; 4. Langmuir monolayers Michael Dennin; 5. Computer modeling of granular rheology Leonardo E. Silbert; 6. Rheological and microrheological measurements of soft condensed matter John R. de Bruyn and Felix K. Oppong; 7. Particle-based measurement techniques for soft matter Nicholas T. Ouellette; 8. Cellular automata models of granular flow G. William Baxter; 9. Photoelastic materials Brian Utter; 10. Image acquisition and analysis in soft condensed matter Jeffrey S. Olafsen; 11. Structure and patterns in bacterial colonies Nicholas C. Darnton.
Includes bibliographical references and index.
Keywords: Soft condensed matter -- Mathematics; Experimental mathematics